Analisis Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Manufaktur Terdaftar di BEI Tahun 2017-2021 - Arumdhani Al’azhmi; Dwiyani Sudaryanti; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted to determine the effect of Profitability, Sales Growth and Liquidity simultaneously affecting the Capital Structure of Manufacturing Companies Registered on the IDX in 2017-2021. This study uses a quantitative approach with the method used in this study is multiple linear regression with the help of SPSS 20 and uses a sample of 30 respondents. The results of this study are the variables Profitability, Sales Growth and Liquidity simultaneously have a positive and significant effect on the capital structure of Manufacturing Companies Registered on the IDX in 2017-2021.Keywords: Profitability, sales growth, liquidity